Reinterpretation of evidence advanced for neo-oogenesis in mammals, in terms of a finite oocyte reserve - Notarianni Elena (BMC, 2011)
Abstract The central tenet of ovarian biology, that the oocyte reserve in adult female mammals is finite, has been challenged over recent years by proponents of neo-oogenesis, who claim that germline stem cells exist in the ovarian surface epithelium or the bone marrow. Currently opinion is divided over these claims, and further scrutiny of the evidence advanced in support of the neo-oogenesis hypothesis is warranted - especially in view of the enormous implications for female fertility and health. This article contributes arguments against the hypothesis, providing alternative explanations for key observations, based on published data. Specifically, DNA synthesis in germ cells in the postnatal mouse ovary is attributed to mitochondrial genome replication, and to DNA repair in oocytes lagging in meiotic progression. Lines purported to consist of germline stem cells are identified as ovarian epithelium or as oogonia, from which cultures have been derived previously. Effects of ovotoxic treatments are found to negate claims for the existence of germline stem cells. And arguments are presented for the misidentification of ovarian somatic cells as de novo oocytes. These clarifications, if correct, undermine the concept that germline stem cells supplement the oocyte quota in the postnatal ovary; and instead comply with the theory of a fixed, unregenerated reserve. It is proposed that acceptance of the neo-oogenesis hypothesis is erroneous, and may effectively impede research in areas of ovarian biology. To illustrate, a novel explanation that is consistent with orthodox theory is provided for the observed restoration of fertility in chemotherapy-treated female mice following bone marrow transplantation, otherwise interpreted by proponents of neo-oogenesis as involving stimulation of endogenous germline stem cells. Instead, it is proposed that the chemotherapeutic regimens induce autoimmunity to ovarian antigens, and that the haematopoietic chimaerism produced by bone marrow transplantation circumvents activation of an autoreactive response, thereby rescuing ovarian function. The suggested mechanism draws from animal models of autoimmune ovarian disease, which implicate dysregulation of T cell regulatory function; and from a surmised role for follicular apoptosis in the provision of ovarian autoantigens, to sustain self-tolerance during homeostasis. This interpretation has direct implications for fertility preservation in women undergoing chemotherapy.